Empirical analysis of android apps permissions - Awang Abu Bakar, Normi Sham; Mahmud, Iqram (2013)
Android applications or apps are taking the smart phones industry to a new level. Smart phone users can do most of their everyday tasks using the various types of applications offered in the Android Play Store. Generally, prior to installation of the apps, users need to agree on the permissions requested by the apps, they are not given any other option. Essentially, users may not aware on some security issues that may arise from the permissions. Some apps request the right to manipulate sensitive data, such as GPS location, photos, calendar, contact, email and files. In this paper, we explain the sources of sensitive data, what the malicious apps can do to the data, and apply the empirical software engineering analysis to find the factors that could potentially influence the permissions in Android apps. In addition, we also highlight top ten most implemented permissions in Android apps.